Intracellular unbound drug concentrations : methodology and application for understanding cellular drug exposure - Mateus, André, 1972- (2016)
Tese de doutoramento (co-tutela), Farmácia (Biofarmácia e Farmacocinética), Universidade de Lisboa, Faculdade de Farmácia, Uppsala Universitet, Faculty of Pharmacy, 2016